Discovery of a rare and striking new pierid butterfly from Panama (Lepidoptera: Pieridae) - Nakahara, Shinichi; Macdonald, John R.; Delgado, Francisco; Padrón, Pablo Sebastián (Zootaxa, 2018)
We here describe and name a distinctive new pierid species in the subfamily Pierinae, Catasticta sibyllae Nakahara, Padrón & MacDonald, n. sp. from western Panama. Catasticta. sibyllae n. sp. is known from only two male specimens collected at two sites which are approximately 130 km apart in western Panama. This new species is the only species in the genus without markings in the median area of both surfaces of forewing and hindwing, and our molecular data suggest that the Peruvian species C. lisa Baumann & Reissinger, 1969 is its sister species.